Peak Ground Acceleration (PGA) Analysis for Eathquake Risk Mitigation in IKN Area, Sepaku Sub-Distric, East Kalimantan - Rahmania, Rahmania; Alfania, Alfania; Sastrawan, Febrian Dedi; Arisalwadi, Meidi (Universitas Islam Negeri (UIN) Mataram, 2024)
This study examines the distribution of Peak Ground Acceleration (PGA) in the Ibu Kota Nusantara (IKN) development area, Sepaku Sub-District, East Kalimantan, an area with relatively low seismic activity compared to other parts of Indonesia. However, earthquake risks remain a concern due to the planned relocation of Indonesia's capital. Using the Kanai approach and seismic data from microtremor measurements and two significant earthquakes (Paser Regency, 2022, and Palu, 2018), PGA values ranged from 0.69 gal to 34.29 gal. The results show that the 4.5 magnitude Paser earthquake produced PGA values between 0.69 and 3.17 gal (average 1.8 gal), placing most areas in the low-risk zone. In contrast, the distant 7.2 magnitude Palu earthquake generated PGA values between 2.9 and 34.29 gal (average 15.6 gal), placing several areas in the moderate-risk zone. These findings underscore the significant impact of earthquake magnitude on PGA, with larger, more distant earthquakes causing stronger ground shaking. In conclusion, despite East Kalimantan's low local seismic activity, the study highlights the vulnerability of the IKN area to strong ground shaking from distant, high-magnitude earthquakes. This underscores the need for continued monitoring and preparedness, with tailored earthquake risk mitigation strategies, including reinforced construction standards and geotechnical assessments, to ensure the region's resilience to both local and distant seismic events. These insights are crucial for integrating seismic resilience into IKN's urban planning and the sustainable development of Indonesia's new capital city.